Efektivitas Penggunaan Dana Bantuan Operasional Sekolah Daerah (BOSDA) di SMP Muhammadiyah 1 Berbah Tahun 2023 - Indrawati, Gista; Fitri Mutmainah, Nur (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2024)
This study analyzes the effectiveness of using Regional School Operational Assistance Funds (BOSDA) at SMP Muhammadiyah 1 Berbah, Sleman, in 2023. This research was conducted through a descriptive qualitative approach, where data was collected through observation, interviews, and documentation. The results showed that BOSDA has effectively improved educational facilities and infrastructure. The BOSDA program is important in improving the quality of education, although it needs more planned management and continuous monitoring to optimize the benefits.